INSULIN ALLERGY: A CASE STUDY - Akhouri Sukrit Prakash (Student's Journal of Health Research, 2023)
BACKGROUND: Hypersensitivity to insulin is uncommon but difficult for diabetics. In light of the advancement of preparations containing human recombinant insulin, the incidence of insulin allergy has decreased. From erythema and edema at the site of the injection to anaphylaxis, hypersensitivity responses might occur. Many reactions are to recombinant insulin itself, even though others are to excipients (such as zinc, protamine, or meta cresol). We present a case of insulin-dependent type 2 diabetes mellitus (T2DM) in which a patient developed type 1 hypersensitivity to several insulin formulations. CASE REPRESENTATION: A 55-year-old woman was referred for assessment of insulin reactions after having insulin-dependent T2DM for 7 years and essential hypertension for 4 years. The patient arrived complaining of many abdominal ulcers at the locations of insulin injections on the belly and thigh. After receiving treatment from a local doctor using Insulin Glargine and OHA, she later developed abdominal ulcers. A village surgeon administered antibiotics. CONCLUSION: Our instance emphasizes the value of establishing a correct insulin sensitivity diagnosis through a thorough history and targeted testing. Avoidance, insulin substitutes, different insulin formulations, and desensitization are all examples of therapeutic approaches. Pancreatic transplantation or the drug omalizumab have both been effective in treating severe recurring hypersensitivity reactions.